The Female Pediatric Surgeon - Dingemann, Carmen (European Journal of Pediatric Surgery, 2017)
In medical schools throughout Europe, women make up an increasing proportion of graduates entering the medical profession. Even though this phenomenon is also found in the surgical profession, women are still clearly underrepresented. However, it has been demonstrated that women are equally qualified as men, and are as eager as men to aim for a surgical career.In general, a career in surgery has significant lifestyle implications for both men and women. In particular, women meet challenges such as pregnancy, maternity, and responsibility for childcare that compete with pressures of time and expectations of productivity. Further complicating the situation, there is a huge complexity of national legislation dealing with maternity and parental leave within Europe. Owing to this legal inconsistency, a strong demand on targeted policies and guidelines has increased particularly among the surgical staff.The scarcity of female role models and mentors has also been discussed as a possible explanation for the underrepresentation of women in academic surgery. Even in the 21st century, the advancement of women into leading positions of academic surgery and major surgical societies is still limited. An updated view of leadership development, the promotion of female surgeons in academic surgery, and identifying barriers to women entering this field are crucial to correcting the existing gender inequities.This contribution aims to highlight the current situation of women in academic surgery, outline findings on gender disparities, and define persistent obstacles to the advancement of women in surgery. In addition, this review presents new possibilities and provides approaches to overcome the underrepresentation of female surgeons. In current literature, there is only little information concerning the situation of female pediatric surgeons. Therefore, this article mainly relies on available data on the female surgeon in general.
Keywords: women; pediatric surgery; career; role models; pregnancy